A Supervisory Control Theoretic Approach to the Analysis of Democratic Progress - Park, Seong Jin; Yang, Jung Min (International Journal of Control, Automation and Systems, 2018)
In this paper, we show that supervisory control theory of discrete event systems can serve as a methodology to analyze the principle of democratic progress. For this purpose, we address a new supervisory control problem in which each local supervisor is designed with its own private specification, and an additional progressive specification is given as a global objective for a system to follow. We present the controllability and power-observability as the main conditions for a controlled system to meet a progressive specification in the sense that the number of local supervisors meeting private specifications increases as the controlled system evolves. We then demonstrate that the developed theory can be used to analyze the principle of democratic progress in a systematical way through a case study of labor unions in the Unites States.
Keywords: Automaton; Controlled system; democracy; Global objective; Labor unions; Supervisory control; Supervisory control theory; Unites state; Automaton; democracy; discrete event system; supervisory control